Bureaucracies and power: Examining the Medical Council of India and the development of emergency medicine in India. (July 2020) - Sriram, Veena; Baru, Rama; Hyder, Adnan A.; Bennett, Sara
Abstract: In many countries, professional councils are mandated to oversee the training and conduct of health professionals, including doctors, nurses, pharmacists and allied health workers. The proper functioning of these councils is critical to overall health system performance. Yet, professional councils are sometimes criticized, particularly in the context of low- and middle-income countries, for their misuse of power and overtly bureaucratic nature. The objective of this paper is to understand how professional councils use their bureaucratic power to shape health policy and systems, drawing upon the recent development of emergency medicine in the context of the former Medical Council of India. We undertook a qualitative case study, conducting 87 interviews, observing 6 meetings and conferences, and reviewing approximately 96 documents, and used the Framework method to analyze our data. The passive exercise of bureaucratic power by the Council resulted in three challenges – 1) Opaque policy processes for recognizing new medical specialties; 2) Insular, non-transparent training policy formulation; 3) Unaccountable enforcement for regulating new courses. The Council did not have the requisite technical expertise to manage certain policy processes, and further, did not adequately utilize external expertise. In this time period, the Council applied its bureaucratic power in a manner that negatively impacted emergency medicine training programs and the development of emergency medicine, with implications for availability and quality of emergency care in India. The successor to the Council, the National Medical Commission, should consider new approaches to exercising bureaucratic power in order to meet its objectives of strengthening medical education in India and ensuring access to high-quality services. Future studies should also explore the utilization of bureaucratic power in the health sectors of low- and middle-income countries in order to provider a deeper understanding of institutional barriers to improvements in health. Highlights: Limited research on the bureaucratic power of health sector professional councils. We studied the Medical Council of India, power and emergency medicine in India. We found several limitations to the application of bureaucratic power by the Council. Technical expertise was not a core aspect of their bureaucratic power. The National Medical Commission can reimagine typical uses of bureaucratic power.